PENINGKATAN LITERASI KESADARAN TERHADAP TATAKELOLA SAMPAH BERBASIS 3R SANUR KAUH, DENPASAR: Increasing Literacy and Awareness of 3R-Based Waste Management Sanur Kauh, Denpasar District - Tantra, I G. Lanang P.; Sara, I Made; Murthi, Ngurah Wisnu (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
Using 3R waste sorting, awareness literacy on waste management aims to raise public awareness on how to manage a cleaner, healthier, and more sustainable environment. The community service implementation method consists of four stages. This consists of an initial stage, a second stage where coordination with waste managers is carried out, a third stage where everything that has been planned and discussed with waste managers is implemented to residents, a third stage where solutions to the most important waste problems in Sanur Kauh village are sought, and a fourth stage where evaluation is carried out. The results of the community service show that awareness literacy on 3R waste sorting is a very important step in creating a clean, healthy, and sustainable environment. This program can be very beneficial for the people of Sanur Village and the surrounding environment if it involves all levels of society. In Sanur Village, the 3R waste sorting program has shown very encouraging results. This village has succeeded in reducing the amount of waste disposed of to the landfill and imp